2004
DOI: 10.1177/0146167204271177
|View full text |Cite
|
Sign up to set email alerts
|

Perspective and Prejudice: Antecedents and Mediating Mechanisms

Abstract: The present work investigated mechanisms by which Whites' prejudice toward Blacks can be reduced (Study 1) and explored how creating a common ingroup identity can reduce prejudice by promoting these processes (Study 2). In Study 1, White participants who viewed a videotape depicting examples of racial discrimination and who imagined the victim's feelings showed greater decreases in prejudice toward Blacks than did those in the objective and no instruction conditions. Among the potential mediating affective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
267
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(284 citation statements)
references
References 29 publications
10
267
0
7
Order By: Relevance
“…These findings also point to important aspects that should be further explored. Future research may focus on different types of perspective taking, such as negotiators' tendencies to focus on the counterpart's preferences and underlying interests, the counterpart's value orientation (e.g., the counterpart's prosocial, egoistic, or competitive motivation; Epley et al, 2006), or on the counterpart's thoughts (Galinsky & Ku, 2004;Galinsky & Moskowitz, 2000) and feelings (Batson et al, 1997;Dovidio et al, 2004). As suggested by recent research (Galinsky et al, 2008), focusing on different psychological states of the counterpart brings about different effects with respect to individual and joint outcomes in negotiations with interlinked issues.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…These findings also point to important aspects that should be further explored. Future research may focus on different types of perspective taking, such as negotiators' tendencies to focus on the counterpart's preferences and underlying interests, the counterpart's value orientation (e.g., the counterpart's prosocial, egoistic, or competitive motivation; Epley et al, 2006), or on the counterpart's thoughts (Galinsky & Ku, 2004;Galinsky & Moskowitz, 2000) and feelings (Batson et al, 1997;Dovidio et al, 2004). As suggested by recent research (Galinsky et al, 2008), focusing on different psychological states of the counterpart brings about different effects with respect to individual and joint outcomes in negotiations with interlinked issues.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In other words, in condition where we have empathy on someone, we tend to conclude the behavior of the person similarly as how the person perceive it. Some studies have shown that attitude towards groups of minority can be improved by creating or stimulating empathy towards the groups (of minority) (Finlay and Stephen, 2000;Vescio et al 2003;Dovidio et al 2004).…”
Section: Empathy and Attributionmentioning
confidence: 99%
“…Böylece ortak noktaların olduğuna işaret eden algı, dış gruba zarar verme olasılığını azaltabileceği gibi zarar verilse bile bu zarar sonucunda kolektif suçluluk hissetme ihtimalini arttırır (Dovidio, ten Vergent, Stewart, Gaertner, Johnson ve Esses, 2004). Kofta ve Slawuta (2013) zarar gören grup ile kültürel (örn., norm ve değerler açısından farklılıklar) bir uzaklık algılandığında iç grubun verdiği zararın hatırlatılmasının düşük düzeyde bir kolektif suçluluğa neden olduğunu bulmuşlardır.…”
Section: Kolektif Suçluluğun Oluşmasını Kolaylaştıran Unsurlarunclassified